Razvoj ustavnosti Rumunije / Development of Romanian Constitutionality - Durmišević, Tarik (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Romania used to establish its institutions in the principality tradition. The first constitutional rule dates back to the 1830s, when during the short Russian rule, Russia granted identical status to the Principalities Walachia and Moldavia. The statutes envisioned the division of power, a prince to be elected by a special state, more precisely the boyar assembly, and the existence of a regular and elected boyar assembly. In time, a Romanian national program was formed, which called for the unification of the two principals under a foreign monarch, with the autonomous representative government. The last Romanian constitution was passed in 1991. It is still in force with the 2003 amendments necessary for Euro-Atlantic integration. The Constitution envisions the return to a democratic system with a general right of vote and a two-house assembly. The political system is a semi-presidential.